University, Inc.: The new global will - Alvarado Dávila, Víctor (2014)
This essay is a critical analysis of the current and pressing problems that beset the university in the age of globalization, highlighting the changes in institutional and academic performance that—thanks to accreditation practices and the homogenization of degrees—transform university autonomy into institutions that favor business interests and protect intellectual property rights.